Rhythmic cilia changes support SCN neuron coherence in circadian clock - Tu, Hai-Qing; Li, Sen; Xu, Yu-Ling; Zhang, Yu-Cheng; Li, Pei-Yao; Liang, Li-Yun; Song, Guang-Ping; Jian, Xiao-Xiao; Wu, Min; Song, Zeng-Qing; Li, Ting-Ting; Hu, Huai-Bin; et al. (Science (American Association for the Advancement of Science), 2023)
The suprachiasmatic nucleus (SCN) drives circadian clock coherence through intercellular coupling, which is resistant to environmental perturbations. We report that primary cilia are required for intercellular coupling among SCN neurons to maintain the robustness of the internal clock in mice. Cilia in neuromedin S–producing (NMS) neurons exhibit pronounced circadian rhythmicity in abundance and length. Genetic ablation of ciliogenesis in NMS neurons enabled a rapid phase shift of the internal clock under jet-lag conditions. The circadian rhythms of individual neurons in cilia-deficient SCN slices lost their coherence after external perturbations. Rhythmic cilia changes drive oscillations of Sonic Hedgehog (Shh) signaling and clock gene expression. Inactivation of Shh signaling in NMS neurons phenocopied the effects of cilia ablation. Thus, cilia-Shh signaling in the SCN aids intercellular coupling. Coordination of physiology with daily rhythms is regulated by the neurons of the suprachiasmatic nucleus (SCN), the central pacemaker of the biological clock. Tu et al . describe a signaling mechanism at cilia in these neurons that keeps the individual cells of the SCN synchronized (see the Perspective by Kim and Blackshaw). The length and abundance of primary cilia in SCN neurons oscillated with daily light-dark cycles. Cilia organize signaling by the morphogen Sonic Hedgehog (SHH), and regulation of the expression of this gene was required for synchrony of the SCN cells. In mice exposed to an altered light cycle to induce experimental jet lag, disrupting SHH signaling allowed the animals to adjust more quickly to the altered environment. —L. Bryan Ray Signaling at cilia helps couple neurons in the master biological clock in the brain.